The Relationship Between Learning Interest and Students' Learning Outcomes in Science at MTs Alkhairaat Pakuli - Nurrahma Jumaliani; Mohammad Jamhari; Raya Agni; Fatmah Dhafir; Hayyatun Mawaddah; Syech Zainal (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aimed to analyze the relationship between students' learning interest and their learning outcomes in Science at MTs Alkhairaat Pakuli using a quantitative correlational research design. The study population consisted of 146 students, with a sample of 107 students selected using the Slovin formula and proportional stratified random sampling technique. Data on learning interest were collected through a Likert-scale questionnaire developed based on the indicators of enjoyment, engagement, attention, and students' interest in Science learning. Meanwhile, data on learning outcomes were obtained from the documentation of students' final Science examination scores. Data were analyzed using SPSS version 27 through the One-Sample Kolmogorov–Smirnov normality test and the Spearman's Rank correlation test. The normality test indicated that the data were not normally distributed (Sig. = 0.000 < 0.05); therefore, the hypothesis was tested using the non-parametric Spearman's Rank correlation. The results revealed a correlation coefficient of 0.026 with a significance value of 0.794 (p > 0.05), indicating a very weak and statistically insignificant relationship between learning interest and students' Science learning outcomes. Therefore, the alternative hypothesis (H?) was rejected, and the null hypothesis (H?) was accepted. It can be concluded that students' learning interest has a very weak and non-significant relationship with their learning outcomes in Science at MTs Alkhairaat Pakuli.